Determinants of hopelessness and depression among Chinese hospitalized esophageal cancer patients and their family caregivers. Issue 11 (23rd May 2013) - Han, Yanhong; Yuan, Jie; Luo, Zhiguo; Zhao, Jing; Wu, Junbo; Liu, Rongying; Lopez, Violeta
Abstract: Background: It has been well documented that the diagnosis of cancer is psychologically devastating to both the patients and caregivers. The incidence and mortality of esophageal cancer were 20.85 and 16.24 per 100, 000 persons and the sixth most commonly diagnosed cancer and the fourth main cause of cancer death in China. We surveyed patients–caregivers dyad and examined the determinants of their depression and hopelessness. Results: The prevalence of depression among patients and caregivers was 52.8% and 47.2%, and the prevalence for hopelessness was 64.4% and 53.9%, respectively Regression models indicate that the variables measured could explain 58.9% and 51.7% of the variance in depression and 66.8% and 45.7% of the variance in hopelessness among patients and caregivers, respectively. Overall, hopelessness was a determinant of depression and vice versa to both patients and caregivers. Conclusion: Esophageal patients' depression and hopelessness could also affect caregivers' depression and hopelessness despite the social support that family caregivers have. Psychosocial interventions should be planned to both Chinese patients and caregivers considering the predictors found in this study. Copyright © 2013 John Wiley & Sons, Ltd.